Abundance, Frequency, Economic Valuation and Polymorphism of Umbonium vestiarium in Pilar Bay: Basis for Environmental and Economic Policy Making - Obligar, Philomel Innocent; Contreras, Eric Esteban; Bunda, Raul (Volume 29, No. 2 (2017), 2021)
Life on earth is exceptionally rich and varied. It can appear in the shape and on the scale of anything from very small bacteria to gigantic animals such as the blue whale. Almost 8 years that common button tops vanished from the beaches of Pilar and only on the year 2015 it re appeared. This study was conducted at 9 barangays in Pilar, Capiz, Philippines to determined the abundance, frequency, economic valuation and polymorphism of Umbonium vestiarium in Pilar Bay. A line transect of 100 meters in every sample site and a four 1 x 1 quadrat was used in collecting the species. A comprehensive matrix was used in identifying the color polymorphism. There were a total of 1915 species of U. vestiarium collected from seven (7) sample sites. The species were abundant in Barangay Natividad followed by Barangay Dulangan, and Balogo .It frequently or commonly occured in every quadrat in Barangay Dulangan, Rosario, Natividad, San Ramon, Casanayan, Balogo and Dayhagan. The average harvesting of Umbonium vestiarium in Baranggay Dulangan were around 35 kgs/day, 45 kgs in Natividad, and, 30 kgs in Balogo. The selling price of Umbonium vestiarium in the municipality of Pilar is Php10.00/glass. There were 33 different morphs observed with 9 distinct band and 18 whorl designs respectively.